Case report and review of the literature: a unique presentation of Blau syndrome in a Palestinian family - Subhi Hnaihen, Sandra; Maswada, Nofouz I. A.; Bahar, Aya Ahmad; Idekedek, Mayar; Abunejma, Fawzy M. (Frontiers in Pediatrics, 2025)
Blau syndrome (BS) is a rare inherited systemic disorder, attributed to a gain-of-function mutation in the nucleotide-binding oligomerization domain (NOD2) gene, which results in the upregulation of pro-inflammatory cytokines. This syndrome was initially described as a classic triad of arthritis, dermatitis, and uveitis. In this article, we report a unique presentation of renal failure in a 13-year-old patient who was diagnosed with BS. Interestingly, the patient had only displayed one of the three classical signs, i.e., arthritis. In our case, she had never had any symptoms of the skin or ocular involvement and had just developed arthritis. As a result, the patient was initially misdiagnosed as a case of Juvenile Idiopathic arthritis (JIA). Hence, it's crucial to consider other possible diagnoses when JIA cannot fully explain the patient's presentation and whenever there's an atypical response to treatment. Furthermore, a detailed family history and further investigations; such as genetic testing may be essential for the diagnosis of BS.